“Oásis no deserto de homens em um mundo de desiludidos”: anticomunismo e municipalismo nas trajetórias do “jornalista” Antônio Machado Sant’Anna (1940-1966) - Carvalho, Yuri Araujo (2019)
The dissertation analyzes part of the trajectories of the journalist, politician and businessman Antônio Machado Sant’Anna, a prominent figure in the history of the city of Ribeirão Preto/SP throughout the 20th century. The time set proposed focuses the period when Machado Sant'Anna was the owner and/or director of the local newspapers A Tarde (between 1940 and 1955) and Diário da Manhã (between 1955 and 1966), when his projects and actions became more profitable. Machado Sant’Anna’s trajectories, aligned with the defense of anticommunism (liberal, Christian and nationalist) and municipalism (decentralization, nationalist and urbanagrarian) have elevated him to prominent positions in political and civil societies, where he has succeeded in consolidating advantageous alliances (despite some skirmishes) with the most varied persons and institutions acting in the regional, state and national dimensions. Based on the Gramscian theoretical-methodological contribution to the integrality of the State and the role of the private hegemony apparatus to guarantee the consensus of the subaltern classes, we will promote approximations to a variety of sources (newspapers, magazines, legislative and repressive documents) to explain the paths taken by Machado Sant’Anna, through which we will broaden considerably the horizons of research, towards the scrutiny of complex and comprehensive projects of maintenance of bourgeois hegemony.